Perceptions of Public Sector Employees on Transformational Leadership Characteristics Which Influencing Job Satisfaction - Al Yahyaee, Omar Rashed Humaid; Mohamad, Mohd Amin (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study on assessing the transformational leadership styles characteristics influencing UAE public sector employees' job satisfaction. The literature review found four common types of transactional leadership styles characteristics: Individualized Consideration, Inspirational Motivation, Idealized Influence, and Intellectual Stimulation, which are considered to influence UAE public sector employees Job Satisfaction. Based on these characteristics, a structured questionnaire survey was conducted among UAE public sector employees to determine their level of influence on job satisfaction. It was found that younger respondents in the general worker category and having lower qualifications and working experiences preferred individualized consideration characteristics from the transformational leader could influence UAE public sector employees' job satisfaction. In contrast, older respondents in middle and top management with higher qualifications working experiences favoured idealized influence and intellectual stimulation characteristics that can influence job satisfaction of UAE public sector employees. It also found that the respondents have ranked Intellectual Stimulation as the most influential transformational leadership style characteristic.